Benedict's Insistence on Rank in the Monastic Community: RB 63.1-9 in Context - Kardong, Terrence (Cistercian studies quarterly, 2007)
The article focuses on the teaching of Saint Benedict on the ranking in the monastic community. His ranking has been based on the Rule of the Master to promote unique form of ascetical competition. However, the basis of the ranking has been doubted by Benedict because of the misguided radical egalitarianism including the dishonesty of a person, lack of communal peace and chaotic place for the individual.